Food-Like Growth Conditions Support Production of Active Vitamin B12 by Propionibacterium freudenreichii 2067 without DMBI, the Lower Ligand Base, or Cobalt Supplementation - Deptula, Paulina; Chamlagain, Bhawani; Edelmann, Minnamari; Sangsuwan, Panchanit; Nyman, Tuula A.; Savijoki, Kirsi; Piironen, Vieno; Varmanen, Pekka (Frontiers in Microbiology, 2017)
Propionibacterium freudenreichii is a traditional dairy bacterium and a producer of short chain fatty acids (propionic and acetic acids) as well as vitamin B12. In food applications, it is a promising organism for in situ fortification with B12 vitamin since it is generally recognized as safe (GRAS) and it is able to synthesize biologically active form of the vitamin. In the present study, vitamin B12 and pseudovitamin biosynthesis by P. freudenreichii was monitored by UHPLC as a function of growth in food-like conditions using a medium mimicking cheese environment, without cobalt or 5,6-dimethylbenzimidazole (DMBI) supplementation. Parallel growth experiments were performed in industrial-type medium known to support the biosynthesis of vitamin B12. The production of other key metabolites in the two media were determined by HPLC, while the global protein production was compared by gel-based proteomics to assess the effect of growth conditions on the physiological status of the strain and on the synthesis of different forms of vitamin. The results revealed distinct protein and metabolite production, which reflected the growth conditions and the potential of P. freudenreichii for synthesizing nutritionally relevant amounts of active vitamin B12 regardless of the metabolic state of the cells.